2022
DOI: 10.1002/fsn3.2816
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of probiotic yogurt and vitamin D‐fortified yogurt increases fasting level of GLP‐1 in obese adults undergoing low‐calorie diet: A double‐blind randomized controlled trial

Abstract: Energy restriction and manipulation of macronutrient composition of the diet are the main approaches that are used by people who aim to lose weight. When such strategies are employed, appetite and endocrine regulators of satiety, such as gut peptides, all are deeply affected. The gut microbiota–brain axis controls energy homeostasis in humans by affecting central satiety and gut peptides. The purpose of this study was to evaluate if the synergistic effect of probiotics and vitamin D in yogurt matrix can modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Consistent with earlier acute and short-term, randomized controlled trials, our results suggest that co-supplementation with vitamin D3 and probiotics can effectively modulate hunger and appetite, particularly in overweight individuals [9,10]. This effect might be attributed to the role of short-chain fatty acids (SCFAs) in activating G-protein-coupled receptors, which are known to enhance the secretion of anorectic hormones such as glucagon-like peptide-1 (GLP-1) and peptide YY, thus contributing to appetite suppression [29,30]. The divergent findings in the literature concerning the influence of probiotics on adiponectin and leptin levels [31][32][33] highlight the complexity of their effects on metabolic regulation.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with earlier acute and short-term, randomized controlled trials, our results suggest that co-supplementation with vitamin D3 and probiotics can effectively modulate hunger and appetite, particularly in overweight individuals [9,10]. This effect might be attributed to the role of short-chain fatty acids (SCFAs) in activating G-protein-coupled receptors, which are known to enhance the secretion of anorectic hormones such as glucagon-like peptide-1 (GLP-1) and peptide YY, thus contributing to appetite suppression [29,30]. The divergent findings in the literature concerning the influence of probiotics on adiponectin and leptin levels [31][32][33] highlight the complexity of their effects on metabolic regulation.…”
Section: Discussionmentioning
confidence: 91%
“…Next, we removed 421 studies due to the following reasons: lack of required data as indicated in the inclusion/exclusion criteria, not having an appropriate control group, and co‐supplementation of probiotics and/or synbiotics with other active ingredients. However, there were some studies that were removed due to having the same sample of participants 60–83 and hence were treated as a single study. Finally, 200 unique RCTs with 220 effect sizes were included for quantitative and qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The rise in anorectic gut hormones, which are crucial for sustained weight loss and a sense of satiety, contrasts with the potential hindrance to sustained weight loss associated with an increase in ghrelin during low-calorie diets. Such dietary practices are likely to enhance the microbiota-gut-brain axis, thereby influencing homeostasis and daily intake regulation [235]. The pathophysiology of Alzheimer's disease is intricately connected with the gut microbiome and deficiencies in various vitamins.…”
Section: Synergistic Effects Of Probiotics and Vitamin Co-supplementa...mentioning
confidence: 99%